Assessment of carrying capacity Sangalaki Island Natural Tourism Park, Berau Regency - Joko Mijiarto; Eva Rachmawati (Foresty Faculty of Hasanuddin University, 2022)
Sangalaki Island Nature Tourism Park (NTP) is one of the tourist destinations in Derawan. As a conservation area, tourism development in Sangalaki Island NTP must pay attention to the carrying capacity of the area. The purpose of this research is to calculate the carrying capacity in the NTP area of Sangalaki Island. The research was conducted in October 2021 through literature studies, field observations, and interviews. The calculation of the carrying capacity is carried out with the concept of Physical Carrying Capacity (PCC). The PCC of the area in Sangalaki Island NTP is 259 people/day with details of beach tourism 77 people, snorkeling 69 people, diving 44 people, tracking 13 people, and animal watching 57 people. The PCC data can be the basis for the manager to determine the maximum number of visits that can carry out tourism activities at Sangalaki Island NTP. Carrying capacity is intended to reduce the impact of tourism development on the ecological aspects of the area. In addition, the application of environmental carrying capacity is a manager's step to apply the concept of sustainable tourism at Sangalaki Island.